2009
DOI: 10.1152/ajprenal.90524.2008
|View full text |Cite
|
Sign up to set email alerts
|

Meprin A metalloproteases enhance renal damage and bladder inflammation after LPS challenge

Abstract: Yura RE, Bradley SG, Ramesh G, Reeves WB, Bond JS. Meprin A metalloproteases enhance renal damage and bladder inflammation after LPS challenge. Am J Physiol Renal Physiol 296: F135-F144, 2009. First published October 29, 2008 doi:10.1152/ajprenal.90524.2008.-Meprin metalloproteases, composed of ␣ and/or ␤ subunits, consist of membrane-bound and secreted forms that are abundantly expressed in proximal tubules of the kidney as well as secreted into the urinary tract. Previous studies indicated that meprin metal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
33
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 56 publications
1
33
0
Order By: Relevance
“…In addition, in this mouse model of sepsis, actinonin also prevented the fall in renal capillary perfusion even when administered after the onset of sepsis injury (15). In response to LPS-induced sepsis, meprin A-deficient mice displayed improved renal function and decreased nitric oxide, IL-1␤, and TNF-␣ levels (68), suggesting that meprin A exacerbated renal injury in response to LPS. Recently, meprin was shown to exacerbate ischemia-reperfusion-induced renal injury in male rats.…”
Section: Discussionmentioning
confidence: 83%
“…In addition, in this mouse model of sepsis, actinonin also prevented the fall in renal capillary perfusion even when administered after the onset of sepsis injury (15). In response to LPS-induced sepsis, meprin A-deficient mice displayed improved renal function and decreased nitric oxide, IL-1␤, and TNF-␣ levels (68), suggesting that meprin A exacerbated renal injury in response to LPS. Recently, meprin was shown to exacerbate ischemia-reperfusion-induced renal injury in male rats.…”
Section: Discussionmentioning
confidence: 83%
“…Nonetheless, the lack of systemic inflammation that is evident in the dKO mice upon colitis induction might arise as a result of defective leukocyte movement between the different hematological compartments in response to the intestinal challenge, thereby resulting in greater susceptibility during the progressive phase of the disease. It has also been demonstrated that meprins alter the integrity of epithelial membrane barriers (38). Meprin B cleaves E-cadherin in the adherens junction and disrupts the integrity of the ability of confluent MDCK cells to exclude dextran (23).…”
Section: Discussionmentioning
confidence: 99%
“…Meprins have been implicated in several inflammatory diseases, for example, meprin-␤ has been reported to be a candidate gene for diabetic nephropathy in the Pima Indian population (38). In an experimental model of urinary tract infection, meprin A has been shown to enhance renal damage and bladder inflammation after LPS challenge (53). In addition, polymorphisms of the human MEP1A gene have been correlated with inflammatory bowel diseases (5).…”
mentioning
confidence: 99%